Reckoning applications of Z-iteration: Data dependence and solution to a delay Caputo fractional differential equation - Zaheer, Salman; Chanda, Ankush; Nashine, Hemant Kumar (Nonlinear Analysis: Modelling and Control, 2024)
In this study, we focus on demonstrating the stability of the three-step Z-iterative scheme within the context of weak contraction mappings as defined by Berinde. Further, we attain results concerning stability, data dependence, and error accumulation of the Z-iterative scheme. This article also includes a comparison of the convergence rates among various established iterative strategies. Several illustrative numerical examples are furnished to validate the accuracy and reliability of our findings. In the same spirit, we present an application that utilises the Z-iterative technique on Banach spaces to attain the solution of a delay Caputo fractional differential equation, building upon our primary findings.